Development, evaluation and implementation of a digital behavioural health treatment for chronic pain: study protocol of the multiphase DAHLIA project. Issue 4 (15th April 2022) - Bartels, Sara Laureen; Johnsson, Sophie I; Boersma, Katja; Flink, Ida; McCracken, Lance M; Petersson, Suzanne; Christie, Hannah L; Feldman, Inna; Simons, Laura E; Onghena, Patrick; Vlaeyen, Johan W S; Wicksell, Rikard K
Abstract : Introduction: Chronic pain affects about 20%–40% of the population and is linked to mental health outcomes and impaired daily functioning. Pharmacological interventions are commonly insufficient for producing relief and recovery of functioning. Behavioural health treatment is key to generate lasting benefits across outcome domains. However, most people with chronic pain cannot easily access evidence-based behavioural interventions. The overall aim of the DAHLIA project is to develop, evaluate and implement a widely accessible digital behavioural health treatment to improve well-being in individuals with chronic pain. Methods and analysis: The project follows the four phases of the mHealth Agile Development and Evaluation Lifecycle: (1) development and pre-implementation surveillance using focus groups, stakeholder interviews and a business model; (2) iterative optimisation studies applying single case experimental design (SCED) method in 4–6 iterations with n=10 patients and their healthcare professionals per iteration; (3) a two-armed clinical randomised controlled trial enhanced with SCED (n=180 patients per arm) and (4) interview-based post-market surveillance. Data analyses include multilevel modelling, cost-utility and indicative analyses. In October 2021, inter-sectorial partners are engaged and funding is secured for four years. The treatment content is compiled and the first treatment prototype is in preparation. Clinical sites in three Swedish regions are informed and recruitment for phase 1 will start in autumn 2021. To facilitate long-term impact and accessibility, the treatment will be integrated into a Swedish health platform (www.1177.se ), which is used on a national level as a hub for advice, information, guidance and e-services for health and healthcare. Ethics and dissemination: The study plan has been reviewed and approved by Swedish ethical review authorities. Findings will be actively disseminated through peer-reviewed journals, conference presentations, social media and outreach activities for the wider public. Trial registration number: NCT05066087 .